PENGELOLAAN KELAS DALAM SETTING PENDIDIKAN MULTIKULTURAL - Ni Putu Laksmi Resti Putri (STKIP Subang, 2022)
The purpose of this research is to find out how teachers manage classes in primary school in a multicultural educational setting. The focus of the research is (1) the teacher's actions in the classroom before, during, and after teaching, (2) the teacher's understanding of multicultural education and its application in classroom management, (3) the student's response to what the teacher has done in the classroom during teaching. The research method used is a case study with a qualitative approach. This research is located in one of the primary schools in the city of Bandung. Data collection is done by observing students and interviewing teachers and students. The results of the research prove that teachers in one of the primary schools in Bandung have applied classroom management in a multicultural education setting. For example, it is seen in the use of various ways by the teacher in managing a multicultural class, namely; using Bahasa Indonesia as a teaching language, setting up chairs and tables for students, showing respect for students, using multicultural games or games, using interesting, multicultural and diverse media when teaching in the classroom. With the management of classes in a multicultural education setting, it is expected that tolerance should be developed in the diversity of Indonesia.